POE LEARNING MODEL: THE EFFECT ON STUDENT SCIENCE PROCESS SKILLS ON THE COORDINATION SYSTEM CONCEPT - Yulianti, Siti Hartini; Juanengsih, Nengsih; Mardiati, Yuke (Universitas Negeri Surabaya, 2018)
This study aims to determine the effect of POE (Predict-Observe-Explain) learning models on students' science process skills on the coordination system concept. This research was carried out in SMA Negeri 9 Tangerang Selatan in the 2017/2018 school year. This research method is quasi-experimental with nonequivalent control group design. Sampling using purposive sampling technique. The study sample consisted of 73 students: 37 experimental group and 36 control group. The research instrument used is a test of science process skills in the form of a description test and observation sheet. The results of data analysis of students' science process skills using ANACOVA, showed that there were significant differences between the experimental and the control group. This shows that there was an effect of the application of the POE (Predict-Observe-Explain) learning model on students' science process skills on the concept of coordination system.